Pembelajaran Student Facilitator and Explaining Berbantuan Alat Peraga untuk Meningkatkan Penalaran dan Pemahaman Konsep Siswa - Aeniah, Aeniah; Putra, Ngurah Made Darma; Nugroho, Sunyoto Eko (UPEJ Unnes Physics Education Journal, 2018)
The reasoning skills and students’ physics concept as the main capital for understanding physics extensively. One of the factors that influence the low reasoning and understanding of concepts is the learning that is delivered in the classroom. This study aimed to find out increase the reasoning skills and students’ physics concept and difference of the SFAE assisted by simple aids and learning SFAE without the simple aids. This study employed true experimental design with pretest - posttest control group design. In the experimental group of improvement were included in the high category while in the control group of improvement included the moderate category. Based on the comparison of t test, there are significant differences of the SFAE assisted by simple aids and learning SFAE without the simple aids.